ECONOMETRIC ASSESSMENT OF THE IMPACT OF TERRITORIAL ECONOMIC CLUSTERS ON REGIONAL COMPETITIVENESS - Ravshanova, Nigora Ravshanova Ulugbek kizi (THE INNOVATION ECONOMY, 2026)
This article examines the impact of regional economic clusters on regional competitiveness using statistical and econometric analysis methods. The study analyzes key indicators of regional economic development, including investment volume, industrial production, and the number of cluster enterprises. A multiple regression model was developed to determine the main factors influencing regional economic growth. The results show that the development of economic clusters plays a significant role in increasing regional competitiveness. In addition, several scientific and practical recommendations for improving cluster development policies are proposed.